Palmitoylation of the GluR6 kainate receptor. - Pickering, D S (1995)
The G-protein-coupled metabotropic glutamate receptor mGluR1 alpha and the ionotropic glutamate receptor GluR6 were examined for posttranslational palmitoylation. Recombinant receptors were expressed in baculovirus-infected insect cells or in human embryonic kidney cells and were metabolically labeled with [3H]palmitic acid. The metabotropic mGluR1 alpha receptor was not labeled whereas the GluR6 kainate receptor was labeled after incubation with [3H]palmitate. The [3H]palmitate labeling of GluR6 was eliminated by treatment with hydroxylamine, indicating that the labeling was due to palmitoylation at a cysteine residue via a thioester bond. Site-directed mutagenesis was used to demonstrate that palmitoylation of GluR6 occurs at two cysteine residues, C827 and C840, located in the carboxyl-terminal domain of the molecule. A comparison of the electrophysiological properties of the wild-type and unpalmitoylated mutant receptor (C827A, C840A) showed that the kainate-gated currents produced by the unpalmitoylated mutant receptor were indistinguishable from those of the wild-type GluR6. The unpalmitoylated mutant was a better substrate for protein kinase C than the wild-type GluR6 receptor. These data indicate that palmitoylation may not modulate kainate channel function directly but instead affect function indirectly by regulating the phosphorylation state of the receptor.